New Modernism for a New Millenium : Works by contemporary Asian Artists from the Logan Collection. - Jana, Reena; Logan, Kent; Limn Gallery, San Francisco (San Francisco : San Francisco Museum of Modern Art, 1999)
Wei Dong ; Fang Lijun ; Fanzhi, Zeng ; Guo Wei ; Jun, Yue Min ; Li Shan ; Liu Wei ; Liu Xiaodong ; Luo Brothers ; Miyajima, Tatsuo ; Morimura, Yasumasa ; Murakami, Takashi ; Song Yonghong ; Song Yongping ; Su Xingping ; Wang Guangyi ; Wang Jinsong ; Xu Yihui ; Yanagi, Yukinori ; Zhang Huan ; Zhang Xiaogang
New Modernism for a New Millenium : Works by contemporary Asian Artists from the Logan Collection on view at Limn Gallery, San Francisco, January 21 to March 7, 1999
Engels
boek
Keywords: Azië